Biogeochemical dataset from 6 gravity cores taken as part of the PROSPECTOMICS project - Ellen Schnabel; Sarah P Esser; Pål Tore Mørkved; Steffen Leth Jørgensen; Alexander J Probst; Jens Kallmeyer; Aurèle Vuillemin; Consortium PROSPECTOMICS (PANGAEA, 2025)
The cruise no. 248 (GS23) of Research Vessel G.O. Sars took place from June 7th to 18th, 2023, covering a transect from Tromsø to Svalbard. During the expedition, we collected a total of 6 gravity cores from the southern Barents Sea at ca. 300 m water depth from three sampling areas, corresponding either to known thermogenic and biogenic gas anomalies (i.e. site 1, site 2) or to pristine seabed as reference (i.e. site 3). Gravity cores were subsampled on board and further conditioned for downstream analyses, namely: pore water geochemistry (ion chromatography, alkalinity titration and spectrophotometry), dissolved gas concentrations (gas chromatography), total cell counts (fluorescence microscopy). Here, we provide the corresponding results covering pore water geochemistry, dissolved gas concentrations, and total cell counts.